2001
DOI: 10.1074/jbc.m107337200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Defects in 11-cis-Retinol Dehydrogenase Mutants Associated with Fundus Albipunctatus

Abstract: Mutations in the gene encoding 11-cis-retinol dehydrogenase (RDH5; EC 1.1.1.105) are associated with fundus albipunctatus, an autosomal recessive eye disease characterized by stationary night blindness and accumulation of white spots in the retina. In addition, some mutated alleles are associated with development of cone dystrophy, especially in elderly patients. The numbers of identified RDH5 mutations linked to fundus albipunctatus have increased considerably during recent years. In this work, we have charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Studies on the related SDR member CRAD1 have confirmed, by independent techniques, that this enzyme has a lumenal topology of the catalytic domain (28,29). Moreover, genetic and biochemical data, as well as computer-based modeling, suggest that these enzymes occur as functional homodimers (29,30).…”
Section: Domain Organization and Topology Of Retinol Dehydrogenasesmentioning
confidence: 83%
“…Studies on the related SDR member CRAD1 have confirmed, by independent techniques, that this enzyme has a lumenal topology of the catalytic domain (28,29). Moreover, genetic and biochemical data, as well as computer-based modeling, suggest that these enzymes occur as functional homodimers (29,30).…”
Section: Domain Organization and Topology Of Retinol Dehydrogenasesmentioning
confidence: 83%
“…These enzymes are located in the ER of RPE cells. Lecithin:retinol acyltransferase and 11-cis-RDH are integral membrane proteins (27,28). The mechanism whereby Rpe65 associates with membranes is the subject of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of a mutation in the RDH5 gene in patients with fundus albipunctatus suggests that reduction in the activity of this enzyme is responsible for the delayed dark adaptation that is seen in this disorder [6]. In vitro experiments showed reduced activity in the enzyme protein produced by mutant 11-cis-retinol dehydrogenase, though knockout mice did not develop yellow-white dot retinal lesions [6,13,14]. It remains to be determined why such characteristic yellow-white dot lesions develop in fundus albipunctatus.…”
Section: Discussionmentioning
confidence: 92%